A narrative review of cross‐sectional and prospective associations between self‐schemas and bipolar disorder. (5th January 2021) - Yang, Yan; Fletcher, Kathryn; Murray, Greg
Abstract: The role of self‐concept in bipolar disorder (BD) has not been well understood. The present review utilizes the notion of self‐schema and interrogates existing research concerning evidence for cross‐sectional and prospective associations between four schema‐like constructs (i.e. trait self‐esteem, dysfunctional beliefs concerning contingent self‐worth, early maladaptive schemas and implicit self‐esteem) and various facets of BD. Existing findings demonstrate various types of involvement of self‐schemas in BD. Of particular clinical relevance, the present review suggests that low trait self‐esteem and dysfunctional beliefs concerning contingent self‐worth are risk factors for ongoing BD symptoms and mood episodes. The present review also yields important yet unaddressed questions with respect to the evaluative content of self‐schemas associated with the hypo/manic phase of BD.